Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Iklim Organisasi Sekolah terhadap Produktivitas Sekolah: Studi Kasus di SMPI Nuurushshibyan (YAPIN) Cileungsi - Efrita Norman; Dzulfikar Dzulfikar; Sarta Sarta (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The problem of education in Indonesia still requires extra attention, both in terms of government policies and internal problems at the school level. The school as an organization is led by a principal who is authorized to apply a certain leadership style for the realization of the school's goals. To achieve the goals of national education and realize the vision of the school, factors are needed that can be successful ranging from leadership, educators, staff, infrastructure, work climate and several factors in it. So that the objectives of this study are: (1) To analyze how much influence the principal's transformational leadership has on school productivity at SMPI Nuurushshibyan Cileungsi; (2) To analyze how much influence the school organizational climate has on school productivity at SMPI Nuurushshibyan Cileungsi; (3) To analyze how much influence the principal's transformational leadership and climate school organization of school productivity at SMPI Nuurshshibyan Cileungsi. This research uses a quantitative approach, using a descriptive study method, which is a method directed at solving problems by explaining or describing what the results of the study are, all populations are made into samples so that they are called saturated samples. The results of this study are; (1) The influence of transformational principal leadership on productivity was highly influential by 36.4%; (b) The organizational climate has a 34.5% influence on school productivity; and (c) For transformational principal leadership and the school's organizational climate both have a 72% effect on school productivity. Keywords: Transformational Principal leadership, organizational climate and school productivity.